Characterization of the complete chloroplast genome of Chenopodium quinoa Willd. Issue 2 (12th December 2017) - Wang, Kangyu; Li, Li; Li, Shaokun; Sun, Honghua; Zhao, Mingzhu; Zhang, Meiping; Wang, Yi
Abstract: Chenopodium quinoa Willd is the main traditional food of Inca aboriginal, which was a native grain in South American andes mountains. It has more than five thousand years of edible and cultivation history. Quinoa is rich of comprehensive nutritional value, therefore, be called as the mother of grain. In this study, the complete chloroplast genome of Chenopodium quinoa Willd was determined by the sequencing of PCR fragments. The complete chloroplast genome of C. quinoa Willd was 151, 169 bp in length and displays a typical quadripartite structure of the large (LSC, 83, 576 bp) and small (SSC, 18, 107 bp) single-copy regions, separated by a pair of inverted repeat regions (IRs, 24, 743 bp each). It harbours 120 gene species, including 87 protein-coding genes, 29 transfer RNA and 4 ribosomal RNA gene species. The overall nucleotide composition was: 31.2% A, 31.5% T, 19.0% C, and 18.3% G, with a total G + C content of 37.3%. Phylogenetic relationship analysis shows that C. quinoa closely related to Chenopodium album .